Education and Social Trust in Transitional China. Issue 2 (14th March 2020) - Wu, Cary; Shi, Zhilei
Abstract : It is commonly held that education generates higher trust in others. In this article we consider how education might affect trust in transitional China where sociopolitical risks are widespread. We adopt an instrumental variable approach utilizing China's two educational reforms–– the Compulsory Education Law (1986) and the University Enrollment Expansion (1999) ––as IVs. Analyzing data from the Chinese Family Panel Studies, we show a causal negative effect of education on trust in China. We also show education and risk awareness interact to shape trust: the negative effect of risk awareness on trust is stronger among the better educated. Taken together, the findings not only contribute to a recent debate on whether modernization has an erosive impact on social cohesion in China, but they also shed light on how education might affect trust differently across sociopolitical contexts.